Regulation of the Rights of the Child in the Constitution of the Republic of Armenia in the Version of 2015 - LUCHTERHANDT, O.; Sargsyan, N. (Bulletin of Yerevan University C: Jurisprudence, 2019)
As a result of amendments of 2015, the Constitution of the Republic of Armenia for the first time provides for the basic rights of the child in a separate article. Paragraph 1 of article 37 of the Constitution is based on the legal concept of promoting the child's autonomy with his/her age and enshrines the right to express an opinion on matters concerning to him/her. Article 37 § 2 of the Constitution provides for the principle of 'the best interests of the child' established in the article 3 of the Convention on the Rights of the Child. This principle is also reflected in article 37 § 3 as a criterion to assess the legitimacy of limiting the child's right to maintain regular personal relationships and to maintain direct contacts with parents. The article analyzes and interprets the provisions of article 37 of the Constitution in the context of constitutional developments, international experience and the legislation of the Republic of Armenia.
Keywords: Constitution, article 37, minor, rights of child, age,maturity, right to be heard, interests of child, matters concerning child, primary consideration, parental care, state care and protection